The Contribution of the Internal Audit to the Management: Study of the Societies of the District of Braga - Sara SERRA; Kátia LEMOS; João NEVES; José TEIXEIRA (Communications of International Proceedings, 2021)
Internal audit promotes a broader and more effective control of the organization, as it examines the accounting, financial and operational controls, and is therefore expected to contribute to the improvement of the entities' management process. Given the above, this research aims to assess the perception of top managers, of Public Limited Companies in the District of Braga (in the North of Portugal), on the contribution of internal audit to management. After the application of a questionnaire survey, it was concluded that top management, in fact, considers internal auditing a management tool for making its decisions. However, only 33.3% of the entities studied have Internal Audit, and the main reason for its inexistence is the fact that the need for its implementation has not been diagnosed. This investigation contributes to highlight the importance of auditing for managers, being innovative in the questionnaire it presents and in the population studied.
Keywords: Internal Audit; Financial Statements; Management; Top Management.